Efficacy of IPM module in against fruit borer (Helicoverpa armigera) on Tomato - Singh, Arvind N; Singh, RK (Vegetable Science, 2011)
Among 23 insect pests reported to be associated with tomato fruit borer, Helicoverpa armigera (Hubner) is most detrimental, inflicting (Amutha and Manisegran, 2005) in different parts of country. With the increasing awareness of environmental problems due to continuous use of chemical insecticide, search of an alternate method become necessary. A number of ecofriendly measures have been developed in India to manage H. armigera which includes use of NSKE, NPV, trap crops and seedling root dip in insecticides. (Anonymous,2001). The plant protection technology through IPM evolved by NARS, has to be validated with farmers. (Singh and Trivedi, 2001). Thus, the present studies were conducted for evaluating the efficacy of IPM module in comparison of chemical insecticide at farmer’s field.